"Ready, willing, and able": Predictors of school mental health providers' competency in working with LGBTQ youth. Issue 4 (2nd October 2019) - Smith-Millman, Mills; Harrison, Sayward E.; Pierce, Lauren; Flaspohler, Paul D.
Abstract: School personnel play an important role in supporting the social-emotional needs of LGBTQ youth. Thus, the current study surveyed 157 school mental health providers (i.e., school psychologists, counselors, social workers) from the Southeastern United States in order to examine providers' knowledge, attitudes, and experiences in working with LGBTQ youth. While a majority reported having provided services to LGBTQ students, participants identified multiple barriers that may hinder their care. A number of key predictors of competency were identified, including provider characteristics and professional affiliation. Results have important implications for building the capacity of schools to meet the needs of LGBTQ students.